PENERAPAN DIGITAL MARKETING DALAM PEMASARAN PRODUK REMPEYEK DI DESA BATTEMBAT - Prita Agustina; Anton; Aditia Kuswanto; Muhammad Agus Sofyan (IAIC (Institut Agama Islam Cirebon), 2022)
In this digital era, many MSME business actors use a digital marketing system. This is done in order to expand the marketing of micro businesses. For MSME business actors who do not use a digital marketing system, it will be difficult to expand their product marketing. The purpose of implementing digital marketing is to help solve problems in marketing peanut brittle food products in Battembat Village. The method in this research uses observation and interview techniques. The intended target is a food product MSME business actor called rempeyek. The results of this study apply the use of digital marketing in the form of social media Facebook and Whatsapp.